Assessment of health status over time by Prevalence and Weighted Prevalence functions: Interface in R. Issue 3 (March 2015) - Cabarrou, B.; Jouin, A.; Boher, J.M.; Kramar, A.; Filleron, T.
Highlights The importance of evaluating complications has been stressed in many publications. Descriptive analysis may not be sufficient to evaluate long-term complications. This paper provides two R functions using Prevalence and Weighted Prevalence. This method considers duration and repetitions unlike conventional methods.